The Influence of Fintech Usage and Financial Literacy on The Performance of MSME with Digital Marketing as The Moderating Variable - Ulan Dari Daulay; Rukiah Lubis; Budi Gautama (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Improving the performance of MSMEs is an important topic to discuss for the success and sustainability of a business. This study aims to examine the effect of using fintech and financial literacy on the performance of MSME firms in the city of Padangsidimpuan, with digital marketing as the moderating variable. This study uses a quantitative approach using the Structural Equation Model (SEM) method with the Partial Least Squares (PLS) alternative. The population of this research is UMKM in Padangsidimpuan City. The sample in this study consisted of 142 SMEs using the Slovin formula. The results of the study show that: (1) the use of fintech has a positive and significant effect on the performance of MSME companies (2) financial literacy has a positive and significant effect on the performance of MSME companies (3) digital marketing has a positive and significant impact on MSME business performance (4) Digital marketing amplifies the impact of fintech deployment on MSME business performance (5) Digital marketing mitigates the impact of financial literacy on MSME business performance. Keywords: Fintech, Financial Literacy, Digital Marketing, Business performance, MSMEs